The Tax Landscape of Split Contracts in Engineering, Procurement, and Construction (EPC) Investments: An In-Depth Study - Muchamad Irham Fathoni (Jurnal Syntax Admiration, 2024)
The study examines tax complexities in Engineering, Procurement, and Construction (EPC) contracts, focusing on Indonesia's regulations. It stresses the importance of segregating contracts to simplify taxation, with Final Income Tax applying mainly to construction services. Challenges arise from offshore and onshore components, like equipment supplies and services, leading to disputes over Permanent Establishment (PE) presence and income attribution. Case studies from Indonesia and India demonstrate different tax interpretations. Indonesia typically taxes EPC contracts as unified, while India focuses on profit attribution within its jurisdiction. The paper highlights the role of Tax Treaties, like the Indonesia-Germany protocol, in determining tax treatment based on activities within each country. It underscores the need for consistent tax treatment through contract segregation, considering jurisdictional activities and relevant Tax Treaties.